Smart grids, smart households, smart neighborhoods – contested narratives of prosumage and decentralization in Berlin's urban Energiewende - Leslie Quitzow (Innovation: The European Journal of Social Science Research, 2022)
Imagined futures implicitly shape how a city's infrastructure develops in the present. Because smart grids are still in the making, it is important to understand which urban futures are being associated with them. This paper asks how urban smart grid futures are being imagined through narratives and material practices in the city of Berlin and which notions of urban community these imagined futures stand for. Drawing on the concepts of socio-technical imaginaries and discourse, the paper unravels how relevant actors envision Berlin's smart grid future, focusing especially on the role of urban “prosumage” and micro-grid-neighborhoods in the everyday production, consumption, and management of electricity in the city. The paper concludes that while one dominant imaginary prevails, this dominant imaginary is built on competing and in part contradictory narratives about the role of households, neighborhoods and the city in urban energy transitions. The analysis is based on a case study of three so-called urban laboratories for the development and implementation of smart grids in Berlin. It draws on policy documents and interviews with relevant stakeholders from Berlin's energy, ICT, and urban development sectors, including representatives of incumbent utility companies, small energy entrepreneurs, public authorities, the research community, and civil society organizations.
Keywords: 300; smart grids; imaginaries; decentralized energy management; urban futures; urban labs‌